TRENDS IN THE ABILITY OF HIGHER-ORDER THINKING SKILLS IN ISLAMIC RELIGIOUS EDUCATION IN MADRASAHS: CASE IN INDONESIA (Architecture Image Studies, 2026)
The rapid development of science and technology in the 21st century requires humans to have high-level thinking skills. In the world of education, HOTS is the thinking ability of students who not only remember but are also expected to be able to develop ideas. This research aims to determine students' higher order thinking skills in solving HOTS-based daily assessment questions on Islamic religious education subjects. Quantitative research with descriptive content analysis approach aims to determine students' higher order thinking skills in solving HOTS-based daily assessment questions on Islamic religious education subjects. The data was collected by giving a description test through the MAN 1 Pekanbaru E-learning application version 4.5.1. The results of the PAP analysis show that the class XI students of MAN 1 Pekanbaru tend to have higher-order thinking skills in the "high" category in solving the C6 cognitive domain questions. The results of the interview show that the students of class XI MAN 1 Pekanbaru tend to have difficulty when making/forming sentences that lead to the completion of C6 cognitive domain questions. Students tend to have higher-order thinking skills in the "high" category even though they still have difficulty when making/forming sentences that lead to the completion of C6 cognitive domain questions.